Presentation: Included and Excluded - Grández Moreno, Félix (1996)
In this issue of Allpanchis we present a set of collaborations that serve as a stimulus to address, from the Andean region, one of the most dramatic and profound phenomena of the contemporary world: the economic, social, political and cultural exclusion of broad swaths of the population. Gathered practically spontaneously, each of these collaborations contributes elements of understanding of a highly complex phenomenon.